FORMATION OF TISSUE-ENGINEERED CONSTRUCT OF CARTILAGE IN VITRO - V. A. Surguchenko; A. S. Ponomareva; L. A. Kirsanova; G. N. Bubentsova; N. N. Skaletskij; V. I. Sevastianov (Вестник трансплантологии и искусственных органов, 2013)
Aim. The goal of this study was to demonstrate the possibility of in vitro formation of tissue-engineered const- ruct of cartilage on the basis of cell-engineered construct composed of biopolymer hydrogel matrix and human adipose-derived mesenchymal stromal cells. Materials and methods. As a biodegradable matrix, the hetero- geneous composition of the implantable gel Sphero®GEL (Biomir Service, Krasnoznamensk, Moscow Region) was selected. To generate cell-engineered construct of cartilaginous tissue human adipose-derived mesenchy- mal stromal cells were mixed with biopolymer matrix Sphero®GEL and cultured in chondrogenesis medium. Results. It was revealed that human adipose-derived mesenchymal stromal cells with biopolymer matrix under chondrogenic conditions generate three-dimensional structures and produce cartilaginous extracellu- lar matrix components: collagen type II and glycosaminoglycans. Conclusion. It was discovered that 3-D structures formed in the process of culture of cell-engineered constructs, began to synthesize the components of the cartilage extracellular matrix. This indicates the initial stage of in vitro formation of tissue-engineered cartilage construct.